Primary Retroperitoneal Mucinous Tumours Diagnosed in Pregnancy: A Case Report and Literature Review - Tahmasebi F; Morje M; Jamall H; Polson A; Deo N (Dove Medical Press, 2019)
Farshad Tahmasebi,1 Mridula Morje,2 Hina Jamall,1 Alexander Polson,3 Nandia Deo1 1Obstetrics and Gynaecology, Whipps Cross University Hospital, London, UK; 2Obstetrics and Gynaecology, St Thomas’ Hospital, London, UK; 3Cellular Pathology, Histopathology, St Thomas’ Hospital, London, UKCorrespondence: Farshad Tahmasebi Flat 20 Charing Cross Mansions, 26 Charing Cross Road, London WC2H 0DG, UKEmail tfarshad@hotmail.comAbstract: We present the case of a pregnant patient who was found to have a primary retroperitoneal mucinous tumour (PMRT). An abdominal mass measuring 11.5 × 9.8 × 8.8cm, initially thought to be of ovarian origin, was found incidentally on ultrasound in a 36-year-old patient at 20 weeks’ gestation. Tumour markers were normal. She underwent an elective Caesarean section at 34 weeks, but the uterus, fallopian tubes and ovaries were normal. The mass was found to be retroperitoneal. A clinical decision was made to avoid further surgical exploration at the time. Following further surgical planning, the patient underwent open resection of the retroperitoneal mass, 6 weeks after her Caesarean section. Histology confirmed a moderately differentiated adenocarcinoma suggestive of a primary retroperitoneal mucinous adenocarcinoma. A literature review following this identified five case reports of PMRT in pregnancy in the last decade. In all cases, the patients underwent tumour resection without adverse pregnancy outcomes. While our patient had an uncomplicated pregnancy, she developed a 2cm lesion suggestive of disease recurrence 15 months post-operatively. A plan was made for surgical resection. PMRT are rare, but can occur in pregnant patients and patients of childbearing age. Tumour resection should be carried out, but where there is no concrete evidence of tumour invasion, the uterus and ovaries should be spared to avoid infertility and menopause. We would recommend early tumour resection, given its potentially aggressive nature.Keywords: primary retroperitoneal mucinous adenocarcinoma, pregnancy